Formulation And Evaluation Of Lip Balm Preparation From Watermelon Seed Extract (Citrullus lanatus) As Lip Moisturizer - Alter Y. Runtu; Soniya Tumuju; Douglas N. Pareta; Andry Natanel; Anggelina A. Pangalila; Adolfina Sumagando; Marshella M. Mokoagouw (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
This study aimed to formulate and evaluate a lip balm preparation containing watermelon seed extract (Citrullus lanatus) as a safe and effective natural lip moisturizer, in response to the increasing demand for plant-based cosmetic products. The extract was obtained using the maceration method, and four lip balm formulations were prepared with extract concentrations of 0%, 3%, 6%, and 9%. The preparations were evaluated through physical characterization tests, irritation assessment, hedonic evaluation, and stability testing over a 10-week storage period. The results indicated that all formulations were stable, exhibited acceptable pH values and melting points, and did not cause irritation. Increasing extract concentration significantly improved spreadability and moisturizing performance, with the 9% formulation receiving the highest preference among panelists. These findings suggest that watermelon seed extract has strong potential as a natural and safe active ingredient for lip care formulations.